Application of quantitative risk assessment in wellbore stability analysis - Gholami, Raoof; Rabiei, M.; Rasouli, V.; Aadnoy, B.; Fakhari, N. (2015)
© 2015 Elsevier B.V. Elastic and strength parameters, together with pore pressure and in-situ stresses are key parameters required to be known for determination of safe mud weight window (MWW) in vertical wellbores. Estimation of these parameters, however, is subjected to wide uncertainties mainly due to lack of adequate calibration information including lab and field test data. While there are literatures on the applications of probabilistic and risk analysis on wellbore stability evaluation, limited numbers of publications report on the impact of the chosen failure criteria in estimation of safe MWW under uncertain condition. In this study, data corresponding to a wellbore located in south part of Iran was analyzed using quantitative risk assessment to consider the effect of uncertainty on estimation of safe MWW using different failure criteria. The results indicated that Mogi-Coulomb and Hoek-Brown are more robust against the uncertainty of input parameters and mud weight used for this wellbore could have slightly been increased to reduce the shear failure of the borehole wall. The uncertainty in the input data might also be very critical for casing design when only a simple margin together with pore and fracture pressures are used to select the grade of the casing against burst or collapse loads. It was also noted based on sensitivity analysis that the maximum horizontal stress is the most effective parameter in estimation of MWW. This emphasizes the importance of a reliable estimation of in-situ stresses for safe drilling. The results presented here are based on a single case study, and further studies are still required to get any ultimate conclusion.